Radiosensitisation of bladder cancer cells by panobinostat is modulated by Ku80 expression. - Groselj, B; Kerr, M; Kiltie, A (2013)
BACKGROUND AND PURPOSE: In muscle-invasive bladder cancer there is an urgent need to identify relatively non-toxic radiosensitising agents for use in elderly patients. Histone deacetylase inhibitors radiosensitise tumour cells but not normal cells in vitro and variously downregulate DNA damage signalling, homologous recombination (HR) and non-homologous end-joining (NHEJ) repair proteins. We investigated panobinostat (PAN) as a potential radiosensitiser in bladder cancer cells. MATERIALS AND METHODS: Clonogenic assays were performed in RT112 bladder cancer cells, and RT112 cells stably knocked down for RAD51 or Ku80 by shRNAi. Resolution of γH2AX foci was determined by immunofluorescence confocal microscopy, cell cycle progression by FACS analysis and protein expression by western blotting. RESULTS: PAN had a greater radiosensitising effect in Ku80KD than RT112 or RAD51KD cells; enhancement ratios 1.35 for Ku80KD at 10nM (IC(20) for Ku80KD) and 1.31 for RT112 and RAD51KD at 25 nM (IC(40) for both). PAN downregulated MRE11, NBS1 and RAD51, but not Ku70 and Ku80, increased γH2AX foci formation in a dose-dependent manner and delayed γH2AX foci repair after ionising radiation. CONCLUSIONS: PAN acts as a radiosensitiser in bladder cancer cell lines, and appears to target HR rather than NHEJ. As muscle-invasive bladder tumours have reduced Ku-DNA binding, PAN could be particularly useful as a radiosensitiser in bladder cancer.